Lubrication effects on the flow of wet granular materials - Xu, Qing; Orpe, Ashish V.; Kudrolli, Arshad (Physical Review E, 2007)
We investigate the dynamics of a partially saturated grain-liquid mixture with a rotating drum apparatus. The drum is partially filled with the mixture and then rotated about its horizontal axis. We focus on the continuous avalanching regime and measure the impact of the volume fraction and viscosity of the liquid on the dynamic surface angle. The inclination angle of the surface is observed to increase sharply to a peak and then decrease as a function of liquid volume fraction. The height of the peak is observed to increase with rotation rate. For higher liquid volume fractions, the inclination angle of the surface can decrease with viscosity before increasing. The viscosity where the minimum occurs decreases with the rotation rate of the drum. Limited measurements of the flow depth were made, and these were observed to show only fractional changes with volume fraction and rotation speeds. We show that the qualitative features of our observations can be understood by analyzing the effect of lubrication forces on the time scale over which particles come in contact.